DILEMMA OF WORLD BANK ACTION IN BIRR DEVALUATION AND ITS EFFECTS ON ETHIOPIA - Prakasa, Tirta Bayu; Mutiara Nabighah Khilmia; Nadiya Ivany Putri (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
The Ethiopian financial crisis has been ongoing for several years, with various economic challenges such as high inflation, foreign exchange shortages, and a growing public debt burden. However, one of the major events that triggered the crisis was the devaluation of the Ethiopian birr (the country's currency) in October 2017, which led to a rapid increase in inflation and caused significant economic hardship for many Ethiopians. The World Bank has been providing financial and technical assistance to the Ethiopian government to help address the crisis and promote sustainable economic growth. This research paper analyzes the World Bank's role in addressing Ethiopia's financial crisis using a combination of qualitative and quantitative research methods. The study includes in-depth interviews with key stakeholders, secondary data analysis of World Bank reports and other relevant documents, and exploratory data research methods to analyze economic trends in Ethiopia. Writer also highlights the value of using a combination of research methods to examine complex economic issues such as Ethiopia's financial crisis. By drawing on multiple data sources and research methods, the study provides a comprehensive understanding of the World Bank's role in addressing the crisis and the broader economic context in which it operates.